Manifestation of Javanese Political Concept in President Soekarno's Leadership Style: A Historical-Cultural Analysis - Aldi Cahya Maulidan; Gian Fajar Gemilang; Anugrah (Criksetra: Jurnal Pendidikan Sejarah, 2025)
This research is motivated by the fact that Javanese political concepts have influenced Indonesian politics from the royal era to contemporary times. The concept of Javanese politics has been an integral part of the Indonesian political landscape for a long time. Rooted in the traditions of the ancient Javanese kingdoms, this concept has a deep influence on the perspective and practice of politics in the archipelago, including Soekarno. This research was conducted using a qualitative literature method with document analysis. The qualitative literature method with document analysis is a research approach that focuses on collecting and interpreting data from various written sources. This method involves systematic review of documents such as books, journal articles, reports, archives, and other written sources relevant to the research topic. The results and discussion of the research explain that the concept of Javanese politics has deep roots in traditional Javanese culture and philosophy. Soekarno, as a son of Java, was greatly influenced by these political concepts. He combined traditional Javanese elements with modern ideas of nationalism and socialism. Soekarno also adopted the Javanese concept of the leader as the "axis" or centre of political and social life in both domestic policy and international relations.